Intelligence Quotient and Academic Achievement: A Correlational Study of Guidance and Counseling Undergraduates - Surtiyoni, Endang; Nurlela, Nurlela; Darmawani, Evia; Irawan, Dendi; Fatricia, Prisca Putri (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Students as academicians must be able to develop science and technology through learning / research. Intlegencia Question (IQ) is one of the potentials that are different from one another. If this potential is managed properly, it will bring good learning outcomes. However, the reality in the guidance and counseling study program of FKIP PGRI University Palembang, the IQ test results show that there are students who have superior intelligence categories, their learning outcomes are lower than students with normal average categories. To examine in depth the relationship between IQ and learning outcomes, the research conducted research on the 2023-2024 batch of students. With the number of respondons 72 people. Using the Culture Fair Intlegency Test (CFIT) with GPA document data achieved by students in the first and second semesters of 2023 2024. The results showed the effect of IQ on learning outcomes (GPA) 1.7% while 98.3% was influenced by other factors. With a simple correlation showing a significant value of the independent variable 0.271 on the dependent variable 3.319. This it is illustrated that IQ has a significant correlation even though it is still low.